1985
DOI: 10.1136/pgmj.61.715.445
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure with polyarteritis nodosa and multiple myeloma

Abstract: Summary:A patient who presented with acute renal failure due to renal cortical necrosis is described. Renal biopsy showed cortical infarction and angiography demonstrated aneurysms in the renal, splenic and hepatic circulations. Concurrently he was found to have an IgA kappa paraprotein with bone marrow changes diagnostic of multiple myeloma. He was treated with haemodialysis, immunosuppressive drugs and plasma exchange but died 3 months after presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Occasional cases of PAN associated with myeloma or paraproteinemia have been described. Williams et a1 (17) reported a patient with acute renal failure who was found to have both PAN and multiple myeloma, and they speculated that these were etiologically related. Bouvet and Delrieu (18) documented the case of a patient with PAN and a biclonal gammopathy who subsequently developed amyloidosis with severe nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional cases of PAN associated with myeloma or paraproteinemia have been described. Williams et a1 (17) reported a patient with acute renal failure who was found to have both PAN and multiple myeloma, and they speculated that these were etiologically related. Bouvet and Delrieu (18) documented the case of a patient with PAN and a biclonal gammopathy who subsequently developed amyloidosis with severe nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis is rarely accompanied by MM. To the best of our knowledge, nine cases of PAN with a complication of MM, including our case, have been reported (7)(8)(9)(10)(11)(12)(13)(14) (Table). The reports show that the mean age of these patients was 54.3 years (range, 37-78 years).…”
Section: Discussionmentioning
confidence: 78%
“…Acute renal failure is a very rare manifestation in PAN; moreover, Samarkos et al [3] stated that most of the reported cases of acute renal failure complicated with PAN were associated with concomitant use of nephrotoxic agents such as contrast media [4,5] or other aggravating conditions such as multiple myeloma [6]. As compared with MPA, in which more active urine sediments are observed because of necrotizing crescentic glomerulonephritis, renal insufficiency in PAN is characterized by mildly active urine sediments, since it is primarily caused by renal ischemia because of luminal narrowing of the mediumsized arteries in the kidney [7] as observed in our case.…”
Section: Discussionmentioning
confidence: 99%